2005
DOI: 10.1038/nature03628
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial somatomotor responses in the macaque monkey homologue of Broca's area

Abstract: In the ventrolateral frontal lobe of the human brain there is a distinct entity, cytoarchitectonic area 44 (Broca's area), which is crucial in speech production. There has been controversy over whether monkeys possess an area comparable to human area 44. We have addressed this question in the macaque monkey by combining quantitative architectonic analysis of the cortical areas within the ventrolateral frontal region with electrophysiological recording of neuron activity and electrical intracortical microstimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
248
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(262 citation statements)
references
References 25 publications
13
248
1
Order By: Relevance
“…In electrophysiological work in non-human primates, a subset of mirror neurons in area F5 were active both when the monkey grasped an object with the hand, and with the mouth . In another study, mirror neurons in the same area (F5), which has been proposed as a monkey homolog of Broca's area in humans (Petrides et al 2005), discharged both when a monkey performed an action and when it was presented with an acoustic stimulus associated with that action (Kohler et al 2002). A similar pattern in humans has been observed in a tempero-parieto-premotor circuit using fMRI (Gazzola et al 2006).…”
mentioning
confidence: 54%
“…In electrophysiological work in non-human primates, a subset of mirror neurons in area F5 were active both when the monkey grasped an object with the hand, and with the mouth . In another study, mirror neurons in the same area (F5), which has been proposed as a monkey homolog of Broca's area in humans (Petrides et al 2005), discharged both when a monkey performed an action and when it was presented with an acoustic stimulus associated with that action (Kohler et al 2002). A similar pattern in humans has been observed in a tempero-parieto-premotor circuit using fMRI (Gazzola et al 2006).…”
mentioning
confidence: 54%
“…Several recent studies revealed that BA 44/45 in non-human primates can be seen as a monkey's homologue of Broca's area 25 , which is crucial for speech control in humans 33 . BA 44/45 shows anatomical similarities, comparable cytoarchitectonics 24 as well as similar cortico-cortical projections as Broca's area 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, functional commonalities have emerged over the past years. Electrical microstimulation in BA 44 elicited orofacial responses 25 , and auditory stimulation evoked distinct patterns of brain activity in BA 44 and 45 only with species-specific vocalizations in awake behaving rhesus monkeys 28,29 that were comparable to responses in the human Broca's area 30 . The vlPFC might thus be ideally positioned to gain cognitive control over call initiation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…BA 44 is clearly identifiable in the human brain and is thought to be a central brain region for human speech processing (Friederici, 2012). Petrides et al (2005) recently described a cytoarchitectonically similar area in macaque monkeys. The subregions in the IFC seem to have equal representation in both the left and the right IFC.…”
Section: Anatomy and Functions Of The Lateral Ifcmentioning
confidence: 99%